Analysis of the Relationship Between Understanding Mathematical Logic and Managerial Decision-Making Effectiveness - Ruisli, Marchesa; Laksma Pradana, Bayu; Brotosaputro, Goenawan; Ramirez, Santiago (Pandawan, 2025)
Managerial decision-making, a cornerstone of organizational success, often relies on logical reasoning to address complex scenarios and develop effective strategies, forming the basis of this research. While logical reasoning has been widely recognized, the integration of mathematical logic as a foundational tool for enhancing decision-making effectiveness has remained underexplored. This study investigates how understanding mathematical logic, particularly propositional and predicate logic, impacts managerial capabilities in analyzing problems, formulating strategies, and implementing decisions. To achieve this, the study employs a quantitative approach, utilizing a survey distributed to 150 managers across diverse industries, with data analyzed using Structural Equation Modeling (SEM) to identify relationships between variables. The findings demonstrate the practical applications of mathematical logic, including its utility in strategic planning for technology firms, operational optimization in manufacturing, and improving decision-making frameworks in healthcare. These insights lead to the understanding that mathematical logic is a valuable tool for strengthening managerial decision-making processes, offering significant theoretical and practical contributions to organizational practices.